Molecular Combination of the Dopamine and Serotonin Scaffolds Yield in Novel Antipsychotic Drug Candidates – Characterization by in vivo Experiments - Schulze, M.; Siol, O.; Robaa, D.; Mueller, F.K. U.; Enzensperger, C.; Fleck, C.; Lehmann, J. (Arzneimittelforschung, 2012)
Serotonin and dopamine play an important role in the aetiology of schizophrenia. Combination of the structural scaffolds of both neurotransmitters in a single molecule lead to aromatic [d,g]-bisannelated azecine derivatives, which have been shown to be nanomolar to subnanomolar dopamine D1-D5 receptor antagonists with a preference for the D1 family. In this work the potential antipsychotic activity of some azecine derivatives was predicted by their dopamine receptor affinities obtained in vitro from radioligand binding experiments and conclusively confirmed in vivo (rats) by applying a conditioned avoidance model. Furthermore, the compounds were tested in vivo for the development of catalepsy, which is a predictive parameter for extra-pyramidal side-effects caused by many antipsychotics. The investigated azecines displayed low cytotoxicity, and the affinities for human dopamine D1-D5 and serotonin 5-HT2 A receptors were in a nanomolar range. In vivo, their antipsychotic activities in the rat model were comparable with those of haloperidol and risperidone, but revealed a 2–5 times better therapeutic range with regard to catalepsy. Preliminary tests for oral bioavailability also revealed promising results for this new class of potential antipsychotic compounds. In conclusion, our in vivo experiments show that aromatic [d,g]-annelated azecines represent a novel and advantageous class of potential atypical neuroleptics.
Keywords: 5-HT2 A receptor; dopamine receptor; azecine; antipsychotic; neuroleptic potency; catalepsy